2019
DOI: 10.1155/2019/9836181
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month Retention in and Impact of Enhance®Fitness on Older Adults in Hawai‘i

Abstract: Introduction. Enhance®Fitness is a low-cost group exercise program designed specifically for older adults (60+ years) to improve physical performance. The Hawai‘i Healthy Aging Partnership, a statewide health promotion initiative, has continuously offered Enhance®Fitness to Hawai‘i’s multicultural population since 2007. This study examined 12-month participation in and impact of Enhance®Fitness on physical performance among older adults in Hawai‘i. Method. Linear mixed-effects models were applied to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
2
1
Order By: Relevance
“…The median class attendance rate of 87% was higher than the 64-75% reported in previous studies of in-person exercise classes for older adults [44,45]. Attendance also exceeded the minimum recommendation of 75% attendance for cancer survivors [29,30].…”
Section: Discussioncontrasting
confidence: 56%
“…The median class attendance rate of 87% was higher than the 64-75% reported in previous studies of in-person exercise classes for older adults [44,45]. Attendance also exceeded the minimum recommendation of 75% attendance for cancer survivors [29,30].…”
Section: Discussioncontrasting
confidence: 56%
“…Consistent with the majority of findings from the literature ( Leahey et al, 2010 , Jiandani et al, 2016 , Jiang et al, 2016 , Babatunde et al, 2017 , Burgess et al, 2017 , Leung et al, 2017 , Stoutenberg et al, 2017 , Alexander et al, 2018 , Tomioka et al, 2019 ), older (over 49 years of age) participants were more likely to complete their first the KHC participation than younger (under 29 years) participants. Obesity and chronic disease rates among Aboriginal Australians increase with age ( Australian Institute of Health and Welfare, 2015 ), with 80% of those 55 or more years old overweight or obese.…”
Section: Discussionsupporting
confidence: 86%
“…Poor retention is a problem because longer time spent in weight-loss programs is associated with better weight outcomes ( Jiandani et al, 2016 ); poor retention may distort study findings, likely biasing toward program effectiveness, and require better retention strategies ( Rae et al, 2013 ). Retention in weight-loss programs is generally associated with older age ( Leahey et al, 2010 , Jiandani et al, 2016 , Jiang et al, 2016 , Babatunde et al, 2017 , Burgess et al, 2017 , Leung et al, 2017 , Stoutenberg et al, 2017 , Alexander et al, 2018 , Tomioka et al, 2019 ), though some studies have found no such association ( Moroshko et al, 2011 , Latner and Ciao, 2014 ). Retention rates have been found to be higher among females ( Jiang et al, 2016 ), but also among males ( Burgess et al, 2017 ) or not associated with gender ( Moroshko et al, 2011 , Stoutenberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation